Editorial - Checci, Daniele; Gornick, Janet (Journal of Income Distribution®, 2018)
The articles included in this special issue of the Journal of Income Distribution are a selection of papers originally presented at the first LIS-LWS Users Conference, hosted by LIS, the cross-national data center in Luxembourg. The conference took place at the University of Luxembourg in Belval, Luxembourg, on April 27- 28, 2017. The submitted papers underwent a process of blind review, and this collection of five articles is the final outcome. Taken as a whole, these articles constitute an interesting overview of the ways in which the research community uses the LIS-LWS Databases, which provide researchers access to microdata on income and wealth, respectively.